Inovasi Teknologi Digital sebagai Penggerak Reformasi dalam Sistem Pendidikan - Sapii Saputra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Digital technology innovation has become the main driver in reforming the education system in the modern era. The use of digital technologies, such as online learning platforms, artificial intelligence, and data-based education management systems, has changed the way education is learned, taught, and managed. These innovations not only increase the accessibility and flexibility of learning, but also enable the personalization of the learning experience for students. This article aims to examine the role of digital technological innovation in driving education system reform, as well as highlighting the opportunities and challenges faced in the transformation process. The results of this research conclude that digital technology innovation has great potential to encourage education system reform, as long as it is accompanied by supportive policies, increasing the competency of teaching staff, and equitable development of technological infrastructure. It is hoped that this reform can create an education system that is more inclusive, adaptive and relevant to future challenges.